The role of education in developing best service management in agro-tourism - Shuib, Ahmad (2011)
Agrotourism which comprises the agriculture and tourism sectors together has to be managed as a business in order to be sustainable. Operators of agrotourism business must shift from being agricultural producers to service providers. Educational agencies play important roles in producing graduates who have, besides the academic qualification, skills to serve customers. This paper will focus on the industrial training programs developed by the higher educational institutes in general and identify the strengths and weaknesses of existing programs. The roles of various stakeholders in the interrelationships to the educational program is also discussed. Several suggestions are given to improve the roles of education in the industrial training programs for agrotourism sector.